Capital markets, derivatives, and the law : evolution after crisis - Rechtschaffen, Alan N.; Trichet, Jean-Claude (New York : Oxford University Press, 2014)
In today's financial world overwhelmed by capital market upheaval, it is important to understand the intricacies of new regulation, and individuals must have a strong foundation in how capital markets function, as well as how financial instruments and derivatives work. This book provides readers with the foundation necessary to make informed, well-reasoned decisions about capital market participation, derivative utilization, and adherence to existing and future regulations.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 29, 2014).
Keywords: Financial instruments -- United States; Derivative securities -- Law and legislation -- United States; Capital market -- Law and legislation -- United States; Securities industry -- Law and legislation -- United States; Global Financial Crisis, 2008-2009.